Effect of co‐treatment of microwave and exogenous l‐phenylalanine on the enrichment of flavonoids in Tartary buckwheat sprouts. (27th October 2022) - Peng, Wenping; Wang, Nan; Wang, Shunmin; Wang, Junzhen; Bian, Zixiu
Abstract: BACKGROUND: Tartary buckwheat is rich in flavonoids. The application of physical processing technology and exogenous materials treatment can effectively promote grain germination and the accumulation of bioactive secondary metabolites. The content of four flavonoids, the activities of key enzymes (phenylalanine ammonia‐lyase (PAL), chalcone isomerase (CHI), flavonol synthase (FLS)) and the expression of key enzyme genes ( FtPAL, FtCHI, FtFLS1, FtFLS2 ) in Tartary buckwheat sprouts treated with microwave and l ‐phenylalanine (l ‐Phe) were investigated, and the relationship between them was analyzed to explore the mechanism of promoting flavonoid accumulation, and to provide a theoretical basis for the development of functional Tartary buckwheat sprout food. RESULTS: Germination can promote the synthesis of flavonoids. The contents of chlorogenic acid and rutin in 7‐day sprouts increased by 13 420.63% and 225.12% compared with seeds, respectively. Under the best treatment condition T3 (microwave 250 W, 90 s, 2.9 mmol L −1 L‐Phe), the specific activities of PAL, CHI and FLS in 5‐day‐old sprouts increased by 47.84%, 53.04% and 28.02% compared with control check (CK), respectively; and the expression of FtPAL, FtCHI and FtFlS1 increased by 39.84%, 24.78% and 33.72% compared with CK, respectively. Correlation analysis showed that the content of flavonoids in Tartary buckwheat sprouts was significantly positively correlated with the specific activities of key enzymes ( P  < 0.01) and dynamically correlated with genes related to the synthesis of three enzymes. CONCLUSION: It suggested that microwave and l ‐Phe treatment may promote the synthesis of flavonoids by promoting the expression of key enzymes genes in phenylpropane metabolism and controlling the activity of key enzymes in phenylpropane metabolism. © 2022 Society of Chemical Industry.